2009
DOI: 10.1111/j.1567-1364.2009.00582.x
|View full text |Cite
|
Sign up to set email alerts
|

Spathaspora arborariae sp. nov., a d-xylose-fermenting yeast species isolated from rotting wood in Brazil

Abstract: Four strains of a new yeast species were isolated from rotting wood from two sites in an Atlantic Rain Forest and a Cerrado ecosystem in Brazil. The analysis of the sequences of the D1/D2 domains of the large-subunit rRNA gene showed that this species belongs to the Spathaspora clade. The new species ferments D-xylose efficiently and is related to Candida jeffriesii and Spathaspora passalidarum, both of which also ferment D-xylose. Similar to S. passalidarum, the new species produces unconjugated asci with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 17 publications
1
60
0
10
Order By: Relevance
“…Previous research (Cadete et al, 2009;Hou, 2012) has shown that all species of the Spathaspora clade isolated from decomposing wood trunks or insects associated with this substrate have converted xylose into ethanol more efficiently than the species of reference Pichia stipitis. Cadete et al (2016) classified some species of Spathaspora as ethanol producers and xylitol producers, according to the main product of xylose metabolism.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous research (Cadete et al, 2009;Hou, 2012) has shown that all species of the Spathaspora clade isolated from decomposing wood trunks or insects associated with this substrate have converted xylose into ethanol more efficiently than the species of reference Pichia stipitis. Cadete et al (2016) classified some species of Spathaspora as ethanol producers and xylitol producers, according to the main product of xylose metabolism.…”
Section: Discussionmentioning
confidence: 93%
“…In fact, the gut of beetles and other insects is considered a hotspot of yeast diversity (Suh and Blackwell, 2004;Boekhout, 2005;Rivera et al, 2009;Cadete et al, 2009Cadete et al, , 2012Urbina et al, 2013;Gouliamova et al, 2015;Cadete et al, 2015Cadete et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Saccharomyces cerevisiae is the most popular yeast for fermenting glucose to ethanol due to its high ethanol production yield and comparatively high ethanol tolerance 4,5 , however S. cerevisiae strains cannot ferment xylose to ethanol. Several yeasts such as Candida shehatae, Pachysolen tannophilus, Brettanomyces naardenensis, C. tenuis, Pichia segobiensis, C. lyxosophila, C. intermedia, C. jeffriesii, Spathaspora passalidarum, Spathaspora arborariae, C. prachuapensis, and Scheffersomyces stipitis have been reported as xylose fermenting yeasts [6][7][8][9][10] . The S. stipitis strain produces significant amounts of ethanol from xylose and it has been studied extensively 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Middelhoven & Kurtzman (2007) identified two novel ascomycetous yeast species from strains isolated from rotten wood. In recent years, new xylose-or cellobiose-fermenting yeast species have been isolated from rotting wood in Brazil and the Atlantic rainforest (Barbosa et al, 2009;Cadete et al, 2009;Santos et al, 2011). In an effort to investigate the biodiversity of yeasts inhabiting rotten wood in the rainforest of Hainan, a tropical island in southern China, a variety of undescribed yeast species were isolated ; two of them have been described previously .…”
mentioning
confidence: 99%